Development of Cardiac Events and Functional Recovery Prediction Models for Pediatric Dilated Cardiomyopathy - Kim, Dong-Hee; Choi, Eun Seok; Kwon, Bo Sang; Park, Chun Soo; Cha, Seul Gi; Baek, Jae Suk; Yu, Jeong Jin; Kim, Young-Hwue; Yun, Tae-Jin (Frontiers in Pediatrics, 2021)
Background Since both the risk of death and the probability of spontaneous functional recovery (FR) coexist in association with pediatric dilated cardiomyopathy (DCMP), management should be based on individualized outcome predictions. Methods A single-center retrospective review of 105 pediatric patients (age at presentation ≤ 18 years) with DCMP, managed between 1994 and 2017, was performed. Logistic regression was conducted to identify variables associated with FR and cardiac events (CEs), i.e., death or heart transplantation (HTPL), within two years after initial presentation. Two outcome prediction models were formulated using these variables. Results Twenty-six (24.8%) and 51 patients (48.6%) experienced FR and CE, respectively, within two years after initial presentation. Predictors of mortality without HTPL were earlier era at presentation (HR: 4.13; 95% CI: 1.88 to 9.06; p < 0.001) and significant TR (≥ moderate; HR: 4.31; 95% CI: 1.26 to 14.77; p = 0.020) in multivariable Cox regression model. Predictors of FR were recent era (HR: 4.49; 95% CI: 1.40 to 14.44; p = 0.012), younger age at initial presentation (HR: 0.98 per 1 month increase; 95% CI: 0.97 to 0.99, p < 0.001), post-myocarditis DCMP (HR: 4.29; 95% CI: 1.32 to 13.93; p = 0.015), and arrhythmia-mediated DCMP (HR: 26.88; 95% CI: 2.61 to 276.70; p = 0.006). Risk factors for CEs was idiopathic DCMP (HR: 2.95; 95% CI: 1.32 to 6.56, p = 0.008). The low-risk group who had higher probability of FR than CE in prediction model had a slightly higher overall survival rate (71.4% vs. 52.2% at 10 years after presentation; log-rank p = 0.09) and a significantly higher HTPL-free survival rate (67.5% vs. 24.9% at 10 years after presentation; log-rank p < 0.001) than the high-risk group. Conclusions Prognostication and management strategies for pediatric DCMP may be enhanced by risk stratification using outcome prediction modeling.